Land use effects of biofuel production in the US - Weiwei Wang; Madhu Khanna (Environmental Research Communications, 2023)
Biodiesel production from soybean has been growing in the United States and although its amount is small by comparison with corn ethanol, its addition to existing demands on land can have nonlinear effects on land use, due to an upward sloping and increasingly inelastic supply of land. It is critical to quantify these effects to inform future policies that may expand production of soy biodiesel. Here we apply a multi-period, partial equilibrium economic model (BEPAM) to determine land use under a validated counterfactual scenario with no biofuel policy or with corn ethanol mandate alone to isolate the extent to which expansion of biodiesel production in the US led to the conversion of Conservation Reserve Program (CRP) acres and other noncropland to crop production, over the 2007–2018 period. We find that the land use change intensity of biodiesel ranged from 0.78 to 1.5 million acres per billion gallons in 2018 which is substantially higher than that of corn ethanol, that ranged from 0.57 to 0.75; estimates at the lower end of these ranges are obtained under the assumption that there is no conversion of permanent pastureland to cropland and better supported by model validation than the upper end of these ranges. The land use change elasticity with respect to changes in land rent was more inelastic for biodiesel than for corn ethanol. The largest levels of expansion in cropland were in Iowa, Minnesota, North Dakota, Kansas, Michigan and Mississippi.